Web-based Question and Answer Method to Improve Student Achievement for Sociolinguistics Course Participants - Sigit Haryanto; Rini Fatmawati; Sumayah; Esa Nabila Umara (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
A teaching method comprises the principles and methods used by teachers to enable student learning and it also has an important role in learning activities. In education, we will find many kinds of it. One of them that still used by the teachers is Question and Answer method. Based on the previous researches found in google scholar, this method is able to be conducted by online and nononline. Almost the results inform that the method is useful and has positive impacts for increasing the comprehension of the subjects. The writer’s research is not far different from the previous researches. The objective of this study is to increase the student’s achievement in sociolinguistics subject by using Question and Answer method based on SIMANTE application. The writer chose it due to the weaknesses of lecturing method. By this method is hoped that it will increase the student’s achievement at sociolinguistics subject. Action Research by using system management test (SIMANTE) application was selected as a method of teaching. Then tests become means of colleting the data. The collected data were analysed by using simple descriptive analysis by counting the increasing from before and after treatment. The results of the research are as follows: 1. Class average increases well, that is 60.3 before action, action in cycle I 69.25, and action in cycle II 74.25. 2. Individual acquisition also increases, 20, 36, and 40/ 3. Class acquisition increases too, 50%, 90%, and 100%. 4. Class category acquisition change, from unfinished to finished. The conclusion is by using SIMANTE application, the student’s achiement in sociolinguistics subject increases significally. Based on the results, the writer suggests that Question and Answer based on SIMANTE application is recommended for alternative method of teaching.